(untitled) (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2015)
Introduction: Delay in diagnosis regarding Tuberculosis (TB) is common in developing country as well as in Bangladesh. Therefore, the aim of the study is to identify the factors which have effects on delay in diagnosis. Methodology: A cross-sectional study was carried out at Rajshahi City, Bangladesh. A total of 384 TB patients were took part in the interview presented in the study areas for seeking treatment. The samples were selected using stratified random sampling with simple random sampling techniques. Descriptive statistics, chi-square test and multivariate logistic regression methods in SPSS were employed in this analysis. Results: The results revealed that around 76.3% patients delay in diagnosis and among them 81.3% pulmonary patients were found delay. Patients’ sex, educational status, area of living, and monthly family income were significantly associated with delay in the diagnosis of TB, as obtained through Chisquare test. Multivariate logistic regression method identified sex, educational status, and monthly family income and first visit before diagnosis as risk factors of diagnostic delay. Conclusion: Massive health education needs to be included in the existing TB control programs to enhance the accessibility of patients in health-care service without delay in diagnosis. DOI: http://dx.doi.org/10.3126/saarctb.v11i2.12435 SAARC J TUBER LUNG DIS HIV/AIDS, 2014;XI(2), Page: 21-28